EVALUASI PERENCANAAN REDISTRIBUSI TANAH OBYEK LANDREFORM - Probo Socowibowo, Mr. (FIA UB, 2012)
The success or failure of the plan is ultimately determined by the evaluation is to see how far the existing plan can be implemented. With the results of these evaluations will be feedback for better planning. Sustainability in the implementation of those plans need to be evaluated to determine the extent of the development of successful land redistribution, especially in the poor district land office, because many cases of land reform object is endless. The purpose is to describe the implementation of Planning Land Redistribution Â Object Landreform in accordance with the procedures appropriate to the target, determine the role of stakeholders in planning land redistribution object landreform, and to determine the barriers and support in carrying out plan land redistribution object landreform. This type of descriptive research using a qualitative approach, which is a type of research that revealed the problem it is in accordance with the reality on the ground. The results showed that in principle the implementation of landreform Object Land Redistribution in Malang in 2010 - June 2012, an increase in farmers income, budgets and the need for adequate human resources.